Effects of dietary supplementation with turmeric rhizome extract on growth performance, carcass characteristics, antioxidant capability, and meat quality of Wenchang broiler chickens - Dingfa Wang (Italian Journal of Animal Science, 2015)
Our study aimed to determine the effect of increasing dietary levels of turmeric rhizome extract (TRE) on performance, carcass characteristics, antioxidant capability and meat quality of Wenchang broiler chickens. Three hundred, 1-day-old Wenchang broiler chickens were brooded together for 2 weeks, then randomly allocated into four treatments with five replicates of 15 birds each. Birds were fed a corn-soybean basal diet supplemented with TRE at 0, 100, 200 and 300 mg/kg for 12 weeks. The results revealed that a TRE-supplemented diet had no significant effect (P>0.05) on the body weight, although birds fed a diet with TRE at 100 and 200 mg/kg had higher average daily weight gains and average daily feed as compared to controls from 9 to 12 week (P<0.05). Also, the addition of TRE at 100 to 300 mg/kg had a better feed conversion ratio compared to controls from week 9 to 12 (P<0.05). Dietary supplementation with TRE at 300 mg/kg increased the breast muscle weight ratio (P<0.05). Meanwhile, dietary supplementation with TRE at 100 to 300 mg/kg reduced the abdominal fat ratio (P<0.05), compared to that of the control group. TRE increased enzymatic activities of superoxide dismutase and glutathione peroxidase, and reduced malondiadehhyde concentrations, compared to the control group. Dietary TRE supplementation at 300 mg/kg decreased the drip loss in both breast muscle and thigh muscles, compared with the control group (P<0.05). In conclusion, dietary TRE supplementation enhanced antioxidant capability, growth performance, breast muscle weight ratio, and reduced the abdominal fat ratio of Wenchang broiler chickens.